APPLICATION OF TECHNOLOGICAL COMPLEX FOR AVIATION CHEMICAL TREATMENT OF CULTIVATED PLANTS - DOVBUSH, TARAS; HEVKO, IVAN; KHOMYK, NADIA; DOVBUSH, ANATOLIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article investigates the conditions for ensuring high-performance operation of agricultural drones during the processing of crops and plantations of agricultural crops. It is established that the coincidence of the time of the technological process of processing plants with drones and the time of active operation of their batteries is mandatory. It was noted that time expenditure can be synchronized by timely recharging or replacing batteries, and for this it is necessary to use a technological complex that will perform service actions related to filling with a working pesticide solution and recharging batteries. It has been established that the correct choice of technological schemes for field cultivation is also important for the productive operation of agricultural drones.The article is devoted to the development of a design of a technological complex for aerial plant processing using agricultural drones and recommendations for synchronizing the time for performing the technological process by agricultural drones depending on the tank volume and the service life of the drone batteries. The developed service ground mobile technological device includes a platform with a system for refueling agricultural drones with working solutions of chemical preparations for treating plants, an agricultural drone fixation mechanism, a battery replacement mechanism, and a charging cradle. After filling the agrodrone's tank and replacing the discharged battery with a charged one, the mobile service automatically unhooks the drone, which takes off and moves in the desired direction to continue the technological process of aerochemical treatment of plants. Structurally, the technological complex for charging drones is safe to operate, and it can also be used to monitor the condition of the aircraft, especially its temperature, to prevent batteries from overheating.. It was noted that when using agricultural drones for chemical treatment of fields, the characteristics of the drones, the size of the fields, and the location of charging stations are important, which are proposed to be equipped with the developed technological complexes.Based on the availability of a constructive development of a technological complex for aerial chemical treatment of cultivated plants, taking into account the technological capabilities of agricultural drones and the results of research related to the time spent on performing the technological process of applying agrochemicals, the use of agricultural drones on fields of various configurations was simulated in accordance with technological schemes for field processing and existing technological complexes for servicing agricultural drones.
Keywords: agrodrone; chemical treatment of plants; spraying; charging station; service ground mobile technological device